Пять новых видов наездников-ихневмонид трибы Tryphonini (Hymenoptera, Ichneumonidae) с острова Тайвань и Дальнего Востока России - Каспарян, Д.Р. (Вестник зоологии, 1993)
5 species are described as new: Oto-blastus townesi sp. n., Polyblcistus (Polyblastus) townesi sp. n., Poly blast us (Cophen-chus) rnarjoriae sp. n., Clenochira orientalis sp. n. (holotype female from Primorskiy Krai, Far East Russia, paratype from Taiwan), Aderaeon townesi sp. n.